P186 Can transabdominal bowel ultrasound accurately detect both small and large bowel Crohn Disease in pediatric patients when compared to MRE?. (21st January 2022) - Hudson, A; Huynh, H Q; Ma, H; Kuc, A; Kim, J; Almeida, P; Carroll, M W; Wine, E; Thompson, A; Isaac, D M
Abstract: Background: Magnetic resonance enterography (MRE) has been the modality of choice to assess small bowel inflammation in patients with Crohn disease (CD). It can also assess large bowel when not feasible to assess endoscopically. Transabdominal bowel ultrasound (TABUS) is an attractive non-invasive tool to assess CD activity. Studies to date have focused on its correlation to large bowel endoscopic findings in adult CD. This study aimed to compare TABUS and MRE in identifying small and large bowel CD in pediatric patients. Methods: Pediatric patients (≤18 years old) seen for suspected CD were prospectively enrolled and underwent baseline TABUS, endoscopy, MRE, blood work and stool studies. The Pediatric Crohn's Disease Activity Index (PCDAI) and Simple Endoscopic Score for Crohn's Disease (SES-CD) were used to assess disease activity. Bowel wall thickness (BWT) was assessed by TABUS and MRE. TABUS measurements were scored with the Simple Ultrasound Activity Score for Crohn Disease (SUS-CD) (0=≤3mm, 1=3–4.9mm, 2=5–7.9mm, 3=≥8mm). Pearson Chi-square was used to compare BWT between TABUS and MRE. Results: 21 patients (71% male) were included, with a median age of 13 years (range 6–16). Median PCDAI was 40 (25–49) and SES-CD 15 (6.5–22). There was a high level of agreement between MRE and TABUS (Figure 1) with some disagreement in the jejunum (n=9/21, 43%). For terminal ileal (TI) disease where there was disagreement, endoscopy of TI was in agreement with TABUS in two patients and MRE in five patients. Endoscopic TI disease that was documented as normal on TABUS was mild (SES-CD 3). In patients with abnormal MRE, BWT was not significantly different between the two modalities (Table 1). In patients with normal MRE, TABUS SUS-CD scores were accurately 0 in almost all segments (score 1 in TI) (Table 2). TABUS correctly identified no fistulae and 2 small bowel strictures (identified at endoscopy), but did not detect 1 intra-abdominal abscess and 4 large bowel strictures (only 1 stricture seen on endoscopy). Excessive lymph nodes (>4) were successfully seen on TABUS in 10/16 patients. TABUS correctly identified 75% of patients with significant mesenteric fibrofatty proliferation. Hyperemia on TABUS corresponded to an abnormal MRE for that segment in 92–100% of small bowel and 50–86% of large bowel. Conclusion: TABUS and MRE are comparable modalities in the assessment of small and large bowel disease in newly diagnosed pediatric CD patients. Assessment of proximal small bowel is complex, and MRE may over-call disease. MRE still plays an important role in assessing abscesses and mild large bowel narrowing. Hyperemia on TABUS is an important indicator of active bowel inflammation, and is particularly useful for endoscopically inaccessible small bowel.